Praksis Penanaman Nilai Local Wisdom Masyarakat Desa Jrahi sebagai Learning Resources IPS - Karim, Abdul (QUALITY, 2022)
The Practice of Instilling Local Wisdom Values for the Jrahi Village Community as Learning Resourcesof Social Studies. Research with locus in Jrahi Village, Gunungwungkal District, Pati Regency, aims to: 1) analyze the praxis of the value of local wisdom of the people of Jrahi Village; 2) assessing the value of local wisdom of the community as a source of social studies learning. The approach in this study is Participatory Action Research – a participatory action research method aimed at identifying research problems based on the needs of the research subject. Researchers as interventionists, activists, and facilitators. The collected data are analyzed qualitatively. The results showed: 1) The praxis of the value of local wisdom of the people of Jrahi Village – such as Sedekah Bumi, Ngalungi Sapi, Barikan, and Dawuhan – became local wisdom that was preserved; 2) The values of local wisdom of the community as a source of social studies learning with the stages of formulating goals, determining material, and making appropriate learning strategies. Penelitian  dengan  lokus  di  Desa  Jrahi  Kecamatan  Gunungwungkal  Kabupaten  Pati,  bertujuan  untuk:  1)  menganalisis  praksis  nilai  kearifan  lokal  masyarakat  Desa  Jrahi;  2)  mengkaji  nilai  kearifan  lokal  masyarakat  sebagai  sumber  pembelajaran  IPS.  Pendekatan  dalam  penelitian  ini  adalah  Participatory  Action  Research  –metode  penelitian  aksi  partisipatoris  bertujuan  mengidentifikasi  problem  penelitian  berdasar  pada  kebutuhan  dari  subjek  penelitian.  Peneliti  sebagai  interventionist,  aktivis,  dan  fasilitator.  Data  yang  dikumpulkan  dianalisis  secara  kualitatif.  Hasil  penelitian  menunjukkan:  1)  Praksis  nilai  kearifan  lokal  masyarakat  Desa  Jrahi  –seperti  Sedekah  Bumi,  Ngalungi  Sapi,  Barikan,  dan  Dawuhan–  menjadi  kearifan  lokal  yang  dilestarikan;  2)  Nilai-nilai  kearifan  lokal  masyarakat  sebagai  sumber  pembelajaran  IPS  dengan  tahapan  merumuskan  tujuan,  menentukan  materi,  dan  membuat  strategi  pembelajaran  yang  tepat.